The influence of age and overweight or obesity on foot sensitivity and postural control: A systematic review - Andreato L.V.* (2020)
© 2020 AJA Inc.Objective: To perform a systematic review on the influence of age and overweight—or obesity—on foot sensitivity, as well as its relationship with balance and postural control. Methods: Publications in the following databases were searched up to December 2018: Cochrane Library, PubMed, Scopus, SPORTDiscus and Web of Science. Both randomised controlled and non-randomised trials, plus cross-sectional studies that evaluated foot sensitivity and balance in adults and/or older people, were investigated. Results: A total of 152 studies were found, 14 studies were included and 506 people of both sexes were involved in the included studies. Conclusions: Increased age represented a detrimental effect on foot sensitivity. Most studies showed that decreased foot sensitivity was related to worse balance and/or postural stability. Overweight or obesity was associated with plantar sensitivity, with lower sensitivity and decreased postural stability observed in obese people.